Chemical composition, in vitro dry matter digestibility, total phenolics and proanthocynidins in bedge lucerne (JJesmenthus virgatus) exotic germplasm - SINGH, SULTAN; NEGI, ARVIND SINGH; AGARWAL, D K; KATIYAR, P K; SINGH, U P (The Indian Journal of Animal Sciences, 2014)
Eighteen genotypes (IL 97-239, -224,-226, -227, -228, -230, -267, -253, -254, -271, -273, -217, -218, -251, -231, -242, -243 and IL 97-257) from exotic germplasm of hedge lucerne grown under uniform agronomic and soil conditions were collected at 50% flowering and evaluated for various nutritional traits. CP contents varied (15.4 to 26.75%) significantly (P